Traço fonológico: variação sob a perspectiva da multilinearidade (Revista de Estudos da Linguagem, 2004)
The concept of natural class delineated in a geometric figure dates back to the Prague School. The idea was incorporated by multilinear phonology. Inserted on phonological different levels and plurilinear lines, dominated by specific categorial nodes, the phonological features are organized hierarchically. Particular context sallow for the occurrence of phonological processes characterizing linguistic variation.In the Portuguese language of Brazil, certain phenomena are explained by the substitution of features registered in related subgroups belonging to a broader category. Other processes allow for the substitution of elements by others in the hierarchy, relating to the degree of aperture and sonority – phonemic reinforcement orweakening. Finally, assimilation and dissimilation are illustrated and can be explained by segmental transparency or opacity. As aconsequence, the geometry of the features re-covers the linguistic variation.